The Influence of Education on the Understanding of Sharia Bank Products and Services - Al Fasiri , Mawar Jannati (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2024)
The public's understanding and knowledge of Islamic banking will certainly influence their decision to become customers of Islamic banks. Consumer knowledge, in this case the community who will become customers, influences their decisions such as what they will use, how much, where to deposit their funds to be managed or stored. This will affect people's behavior and perceptions of Islamic banking and Islamic economics. With high public understanding, it will bring people to trust Islamic bank customers. The objectives of this study are as follows: to find out how education influences understanding of Islamic bank products and services; to find out how much influence education has on understanding Islamic bank products and services. In this study using quantitative methods. Data collection techniques in this study using a questionnaire or questionnaire. This study uses data analysis techniques with (1) research instrument tests in the form of validity tests, reliability tests, and normality tests. (2) simple regression test and (3) hypothesis test in the form of t test.The results of the study stated that there was a positive and significant effect of education on understanding Islamic bank products and services. This was evidenced by the results of the t test stating that with a p-value (sig.t) t count > t table, namely 12,618 > 1.655. This means that Ho is rejected and Ha is accepted, thus there is an influence of the education variable on the understanding variable of Islamic bank products and services. The magnitude of the influence of education on the understanding of products and services of Islamic banks is 51.8%. This shows that education is very important for the community to understand everything, one of which is to understand the products and services of Islamic banks. By understanding the products and services of Islamic banks, the public can choose which products and services can be used for the needs of the community.